MRI Lesion State Modulates the Relationship Between Serum Neurofilament Light and Age in Multiple Sclerosis. Issue 2 (21st January 2021) - Rosso, Mattia; Healy, Brian C.; Saxena, Shrishti; Paul, Anu; Bjornevik, Kjetil; Kuhle, Jens; Benkert, Pascal; Leppert, David; Guttmann, Charles; Bakshi, Rohit; Weiner, Howard L.; Chitnis, Tanuja
ABSTRACT: BACKGROUND AND PURPOSE: Serum neurofilament light (sNfL) has been studied as a biomarker of disease activity in multiple sclerosis (MS). Several factors, including age, can influence its dynamics, and several studies have shown that sNfL increases with age in controls. Our objective was to explore the relationship of sNfL and age at different MS disease stages, including remission and after a gadolinium‐enhancing (Gad+) lesion. METHODS: We included 94 patients with MS with annual sNfL measurements performed with a single‐molecule array assay. We used multivariable linear mixed‐effects models with random intercept to test the association between age and sNfL during remission and after a Gad+ lesion (ie, within 90 days after the Gad+ lesion). The model was adjusted for medication use and sex. RESULTS: We report a positive association between sNfL level and age during remission (adjusted estimate = 1.18% yearly increase, 95% CI = .34‐2.03%, P = .008). In contrast, a negative interaction between age and Gad+ lesion status was observed (adjusted estimate = −1.73%, 95% CI = −2.85 to −.58%, P = .004). CONCLUSION: We propose that younger patients experience a greater elevation in sNfL than older patients in response to Gad+ lesions. Our study provides potential insights into the effects of aging on neuroinflammation in MS.